PENYIDIKAN TINDAK PIDANA PENCEMARAN NAMA BAIK MELALUI MEDIA ONLINE BERDASARKAN UNDANG-UNDANG NOMOR 19 TAHUN 2016 TENTANG PERUBAHAN ATAS UNDANG-UNDANG NOMOR 11 TAHUN 2008 TENTANG INFORMASI DAN TRANSAKSI ELEKTRONIK OLEH DIREKTORAT RESESRSE KRIMINAL KHUSUS POLDA RIAU - Yogi Aditya Perdana; Erdianto '; Widia Edorita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
Criminal acts constitute a criminal act that can be sentenced, any act that is threatened as a crime, a violation of either the Criminal Code or any other legislation. The defamation law or defamation through social media is a special criminal act whose legal sanction is regulated outside the Criminal Code, namely Law number 19 of 2016 regarding the amendment to Law Number 11 Year 2008 concerning Information and Electronic Transactions, as mentioned in Article 27 paragraph (3) stating: